Profesionalisme Guru Dalam Perspektif Al-Quran Tafsir Surat Ali Imran Ayat 164 - Nurchamidah, Nurchamidah; Azizah, Nurul; Syafaruddin, Baso; Hamsah, Muhammad; Rosyad, Ali Miftakhu (Jurnal Progress: Wahana Kreativitas dan Intelektualitas, 2023)
This research aims to analyze the role of teachers in learning, including as facilitators, motivators, boosters, learning engineers, research, service providers and providers of learning inspiration for students. This research uses a literature review method. Data sources in this research are books, journals and research results. The results of the research show that teacher professionalism that every teacher should pay attention to and do is: (1) reciting Allah's verses in every lesson, (2) purifying students from damaged aqidah, from despicable morals, changing and perfecting their reasoning power. through divine knowledge, (3) teaching the Bible and wisdom, so a teacher must know the needs of students and the most basic way for Muslims to learn to write is based on the obligation to write the Koran, understand and practice it.